Kelelahan Kerja pada Pekerja di PT. Indonesia Power Unit Pembangkitan dan Jasa Pembangkitan (UPJP) Priok - Eka Dhiffa Safira; Rafiah Maharani Pulungan; Cahya Arbitera (Jurnal Kesehatan, 2020)
Work fatigue is an important problem that needs to be resolved because can cause work accidents and can have an impact on workers' health. Based on the result of interviews in early 2020, there was one worker who was unconscious due to work fatigue where a similar case had never happened before in the last 5 years. Workers complain of feeling dizzy, tired all over, fever, frequent drowsiness, trembling, feeling heavy in the head, and feeling thirsty while working. The purpose of this study was to identify the factors associated with work fatigue at PT. Indonesia Power Unit Pembangkitan dan Jasa Pembangkitan (UPJP) Priok. This research was a quantitative-analytic study with a cross-sectional design. The population of this research was 81 workers consisting of 11 workers in the main workshop and 70 workers in the mechanical part. The sample of this research was 40 workers in the main workshop and mechanics section which were obtained by a purposive sampling technique. The results show that 57,5% of workers have experienced a high category of work fatigue. Statistical analysis shows that nutritional status (p-value=0,034) and sleep quality (p-value=0,028) were related to work fatigue, while the length of work (p-value=0,299), workload (p-value=0,100) and age (p-value=1,000) were not related to work fatigue. Therefore, workers were suggested to consume foods with high carbohydrate content, adequate-protein, calorie intake, and vitamins, as well as regulating duration and hours of sleep following the Ministry of Health's standards, namely 7-8 hours per day for adults (ages 18-40 year).